Enterprises Among Scheduled Castes in India: An Emerging Scenario - Rajesh, I. D. (SEDME (Small Enterprises Development, Management & Extension Journal), 2024)
This article examines the characteristics of entrepreneurship among Scheduled Castes (SCs) in India using the 5th (2005) and 6th (2013) Economic Census data of the Central Statistical Office. The study employs the method of shift-share analysis to compare the growth of the enterprises at all India levels with that of SC-owned enterprises. The analysis reveals that the number of SC-owned enterprises has been increasing, with a significantly higher rate of change compared to the previous period. However, the prevalence of under-representation of SCs in the business field continues. The wholesale and retail trade, manufacturing and livestock are the three major activities in which SCs were concentrated. The emergence of new SC entrepreneurs has been influenced by several motivational factors, while there are also several factors that have a negative impact on the existence of SC entrepreneurs.
Keywords: Business; Economic Census; SC Entrepreneurs; Shift-Share; Under-Representation; Entrepreneurship